2020
DOI: 10.1007/s10578-020-01031-3
|View full text |Cite|
|
Sign up to set email alerts
|

The Bright Side of Grit in Burnout-Prevention: Exploring Grit in the Context of Demands-Resources Model among Chinese High School Students

Abstract: This study contributes to understanding students’ emotional responses to academic stressors by integrating grit into the well-established Job Demands-Resources Model and by examining the relationship between academic demands, grit (consistency of interests, perseverance of effort), burnout, engagement, academic achievement, depression, and life satisfaction in Chinese students. We conducted a self-report study with N = 1527 Chinese high school students (Mage = 16.38 years, SD = 1.04). The results of structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 66 publications
2
45
0
3
Order By: Relevance
“…Regarding optimism and pessimism, students who reported higher levels of optimism also reported higher levels of satisfaction with all three basic psychological needs as well as higher levels of academic engagement, whereas students who reported higher levels of pessimism reported lower levels of basic psychological need satisfaction. This is in line with Student Demands-Resources assumptions (Salmela-Aro and Upadyaya, 2014;Teuber, 2021) as well as recent empirical findings (e.g., Teuber et al, 2021a;Teuber et al, 2021b) indicating that personality traits (e.g., optimism and pessimism) play an important role in academic and psychological adjustment also in critical situations such as the COVID-19 outbreak (e.g., Martin-Krumm et al, 2020). Our findings suggest that optimistic students are more resistant to social distancing and its associated consequences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding optimism and pessimism, students who reported higher levels of optimism also reported higher levels of satisfaction with all three basic psychological needs as well as higher levels of academic engagement, whereas students who reported higher levels of pessimism reported lower levels of basic psychological need satisfaction. This is in line with Student Demands-Resources assumptions (Salmela-Aro and Upadyaya, 2014;Teuber, 2021) as well as recent empirical findings (e.g., Teuber et al, 2021a;Teuber et al, 2021b) indicating that personality traits (e.g., optimism and pessimism) play an important role in academic and psychological adjustment also in critical situations such as the COVID-19 outbreak (e.g., Martin-Krumm et al, 2020). Our findings suggest that optimistic students are more resistant to social distancing and its associated consequences.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the Job Demands-Resources Model has been successfully adapted to school (Salmela-Aro and Upadyaya, 2014;Teuber et al, 2020;Teuber et al, 2021a;Teuber et al, 2021b) and higher educational (Gusy et al, 2016;Niewöhner et al, 2021) contexts, which was also renamed as Student Demands-Resources Model (for an overview, see Teuber, 2021). Previous findings show that across Eastern and Western education systems, students' personal strengths such as optimism (Teuber, 2021), self-efficacy (Salmela-Aro and Upadyaya, 2014;Teuber et al, 2020;Teuber, 2021), and grit (Teuber et al, 2021b;Tang et al, 2021) decrease negative emotional responses to academic stressors and foster students' engagement in academic work (i.e., the state of energy, dedication, and absorption; (Schaufeli et al, 2002;Salmela-Aro and Upadaya, 2012) and ultimately contribute to academic success and decrease the risk of school dropout (e.g., Bask and Salmela-Aro, 2013).…”
Section: Job/student Demands-resources Theorymentioning
confidence: 99%
“…Firstly, our results underline the importance of promoting resilience in the school context to foster students' engagement and prevent maladjustment. Several authors, indeed, have shown the effectiveness of resilience-based interventions to foster students' well-being (e.g., [71,72]).…”
Section: Discussionmentioning
confidence: 99%
“…Our decision to focus solely upon emotional exhaustion limits the degree to which our findings generalize to other dimensions of burnout that can exist in academic settings (e.g., cynicism and professional efficacy; Schaufeli et al, 2002 ). Indeed, future research might benefit from assessing relationships between grit and various dimensions of burnout (e.g., reduced sense of accomplishment, physical/emotional exhaustion, and activity devaluation) to determine the extent to which heightened grit might act as a protective factor against burnout resulting from exposure to environmental (or workload) demands in different achievement settings ( Teuber et al, 2021 ). Finally, we acknowledge that this study employed a sample of student-athletes who were studying for a 3-year undergraduate degree at a single university in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%